Exploring paruresis (‘shy bladder syndrome’) and factors that may contribute to it: a cross-sectional UK survey study - Hayley Hutchings (BMJ Open, 2024)
Objectives: To assess the prevalence and severity of paruresis (‘shy bladder syndrome’) in a population of university staff and students and to determine if there was any relationship between demographics, self-esteem, presence of social anxiety disorders and negative toilet experiences and paruresis. Design: We undertook an anonymised cross-sectional online survey using Microsoft Forms. We invited participants aged 18 and over to complete the survey which included demographic information; any pre-existing medically or self-diagnosed anxiety-related conditions; Shy Bladder Scale (SBS); Rosenberg Self-Esteem Scale (RSES) and questions about using school toilets in their younger life. We defined ‘mild’ and ‘severe’ paruresis based on total SBS cut-off scores of greater than or equal to 31 and greater than or equal to 40. We calculated prevalence of paruresis, and explored differences in self-esteem, school toilet experience and social anxiety disorders between individuals with and without paruresis. Multivariable logistic regression was used to determine which variables had any influence on having a ‘mild’ and ‘severe’ paruresis diagnosis. Setting: We distributed the survey to all staff and students via their university email address as well as promoting the survey on university social media sites. Results: We received responses from 356 individuals. Most participants (237, 66.6%) were within the 18–30 year age category and most (277, 77.8%) were white. There were 221 (62.1%) females, 119 (33.4%) males and 16 (4.5%) other genders. The prevalence of ‘mild’ paruresis was 25.8% and of ‘severe’ paruresis 14.9% in this sample. 73.0% indicated that they had at least one medically or self-diagnosed anxiety disorder. There was a statistically significant difference in the total SBS score between individuals with and without an existing anxiety disorder (8 vs 19, <0.001). The adjusted odds of ‘mild’ paruresis were higher for men than women (OR 3.39; 95% CI 1.90 to 6.06), lower for those with a lower RSES score (OR 0.90; 95% CI 0.85 to 0.96), lower for those for a lower school toilet experience score (OR 0.88; 95% CI 0.78 to 0.99) and higher for those with at least one anxiety disorder (OR 3.164; 95% CI 1.52 to 6.59). The adjusted odds of ‘severe’ paruresis were higher for men than women (OR 2.60; 95% CI 1.32 to 5.12), lower for those with a lower RSES score (OR 0.90; CI 0.84 to 0.97) and higher for those with at least one anxiety disorder (OR 2.99 (1.18–7.56)). Conclusion: Large organisations should consider measures to help manage anxiety and improve toilet experiences. These could include resources and signposting to manage anxiety disorders and single-occupancy toilets and toilets in quiet areas to limit anxiety associated with shy bladder syndrome.